(untitled) (AWKA JOURNAL OF ENGLISH LANGUAGE AND LITERARY STUDIES, 2023)
There is a seeming gross insensitivity of the Nigerian government to the plight of the many victims of Boko Haram who go through serial abuse, torture, and exploitation in both the Sambisa forest and the IDP Camps. This paper crucially examines the consequences of the Boko Haram mayhem on the female, particularly, young school girls. Deploying Feminist and Marxist theoretical paradigms, this study examines the painful experiences of Cole’s female characters as victims of the Boko Haram activities in Embers. Data for this study is collected primarily through a content analysis of Soji Cole’s Embers, and secondary sources that include essays and books, both print and online. The study reveals that in the face of the heinous practices as seen in the play, the female victims suffer double exploitation - both in the hands of the Boko Haram terrorists, and their supposed ‘rescuers’ in the IDP camps, who randomly exploit these girls sexually. Another finding of this study is that there is a growing suspicion that some Nigerian politicians indirectly sustain the ‘dirty business’ since it avails them the unwholesome opportunity to further exploit the victimized school girls. The paper also reveals that the society - enabled by patriarchal structure - significantly contributes to the nightmares of the female group. It is therefore the dramatist’s perception that the experiences of the female characters as reflected in the play remain a microcosmic representation of the larger experiences of the colossal Boko Haram victims in Nigeria. The study finally concludes by noting that the female group can synergise to combat their exploitations through a necessary revolution to regenerate their human essence, and engineer social recuperation.